Azerbaycan Lenkeran Bölgesi coğrafi etüdü - Şahan, Levent (My University, 2010)
Lenkeran Bölgesi, Azerbaycan’ın beş coğrafi bölgesinden birisidir. Azerbaycan’ın güneyinde yer alan bölge, ülke yüzölçümünün % 7’sini oluşturur. 6.070 km.² alana sahip Lenkeran Bölgesi’nin güneyi ve batısında İran, doğusunda Hazar Denizi bulunur. Lenkeran Bölgesi’nin relief, tarım, hayvancılık, turizm ve iklim özellikleri bakımından çok zengin bir potansiyele sahip olması, bölgenin önemini artırmaktadır. Tarımsal faaliyette sebze, meyve, çay, pirinç, tahıl ve turunçgil üretimi başta gelmektedir. Dağlık alanlarda hayvancılık faaliyeti yapılır. Günümüzde turizm, balıkçılık ve transit nakliyat hızla gelişmektedir. Hirkan Milli Parkı ile Kızılağaç Milli Parkları bölge sınırları içindedir. Ülke genelinde olduğu gibi bölgede de çok hızlı bir gelişme ve ilerlemeyi görmek mümkündür. Lenkeran Bölgesi ile ilgili güncel istatistikî verilerin kullanılması sağlıklı bir değerlendirme sunmaktadır. Lenkeran Bölgesi’ni fiziki ve beşeri coğrafya özelliklerini inceleyen bu çalışma coğrafi araştırma metotları çerçevesinde hazırlanmıştır.

Lenkeran Region is one of the geographical regions of Azerbaijan. The region, which is located in the south of the country, forms % 7 of Azerbaijan’s surface area. It has 6.070 km.² area and is surrounded by Iran in the south and west, and Hazar Sea in the east. Since Lenkeran Region has a rich potential in terms of agriculture, tourism, cattle-breeding, climate and land, the importance of the region has increased up till today. In agricultural activity, the most important products are vegetable, fruit, tea, rice, cereals and citrus. In the mountainous regions, cattle-breeding is done. Nowadays tourism, fishing and transit transport have also been developing rapidly. Hirkan National park and Kızılağaç National parks are located in this region. As in the country, it is also possible to see rapid development and progress in the region. The statistics used related to Lenkeran Region have been obtained from the last data. This study, which examines the physical and human characteristics of Lenkeran Region, has been prepared in the light of geographical research methods.
Keywords: Azerbaycan_Coğrafya; Coğrafya